2017
DOI: 10.1088/1674-1056/26/12/128201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of elastic strain energy on grain growth and texture in AZ31 magnesium alloy by phase-field simulation

Abstract: A phase-field model is modified to investigate the grain growth and texture evolution in AZ31 magnesium alloy during stressing at elevated temperatures. The order parameters are defined to represent a physical variable of grain orientation in terms of three angles in spatial coordinates so that the grain volume of different order parameters can be used to indicate the texture of the alloy. The stiffness tensors for different grains are different because of elastic anisotropy of the magnesium lattice. The tenso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…However, it is difficult and costly to perform a quantitative research by an experimental method due to the influence of disturbing factors and the difficulty in controlling the orientation in a system with massive grains. Computational sim-ulation is an effective way, which can study microstructure evolution, such as grain growth, [7][8][9] texture evolution, [10,11] and precipitation, [12][13][14][15] and also predict thermomechanical response during processing. [16,17] Owing to its advantages such as simulating microstructure on a mesoscopic scale and avoiding tracking the interface explicitly, the phase field model is widely used for crystal evolution.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult and costly to perform a quantitative research by an experimental method due to the influence of disturbing factors and the difficulty in controlling the orientation in a system with massive grains. Computational sim-ulation is an effective way, which can study microstructure evolution, such as grain growth, [7][8][9] texture evolution, [10,11] and precipitation, [12][13][14][15] and also predict thermomechanical response during processing. [16,17] Owing to its advantages such as simulating microstructure on a mesoscopic scale and avoiding tracking the interface explicitly, the phase field model is widely used for crystal evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it was concluded that residual stress changed the transformation texture from <111>// X 0 to <101>// X 0. According to the study by He et al, [ 40 ] the inhomogeneity of elastic strain energy was the fundamental reason for the formation of the texture. It was analyzed that the change in the transformation texture in this article was due to that residual stress affecting the elastic strain energy state of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the phenomenological study of material constitutive model, the two mechanisms require the different damage initiation criteria. [27,28] The ductile criterion is a phenomenological model for predicting damage caused by nucleation, growth, and coalescence of pores. The model assumes that the equivalent plastic strain εpl D at the beginning of the damage is a function of the triaxial stress and strain rate, that is εpl D (η, εpl ).…”
Section: Elastoplastic and Damage Constitutive Model Of Materials Mic...mentioning
confidence: 99%